Investigating the Impact of Auditor Independence, Professionalism, Competence, and Ethics on Audit Quality in the Inspectorate of West Java Province - Budiman, Arief (Maksi, 2023)
Many government agencies currently do not adhere to applicable standards, resulting in issues such as corruption, irregular work practices, abuse of authority and position, and violations. Weak internal control in government operations leads to ineffective outcomes and financial losses for the state. The Government Internal Supervision Apparatus (APIP), specifically the Inspectorate, is responsible for internal control and audits in the government. One of the objectives of the audit process is to produce high-quality audit reports, which can be influenced by factors such as auditor independence, professionalism, competence, and ethics. This study focuses on auditors in the Inspectorate of West Java Province, involving 70 auditors and employing descriptive research methods with a quantitative approach. Primary data was collected through a questionnaire. The study aims to examine the influence of auditor independence, professionalism, and competence on audit quality in the Inspectorate of West Java Province, both before and after considering auditor ethics as a moderating variable. The study utilizes moderating regression analysis as the technical analysis method. The results indicate that auditor independence, professionalism, and competence have a significant impact on audit quality, both individually and collectively. Moreover, auditor ethics, as a moderating variable, enhances the effects of auditor independence, professionalism, and competence on audit quality.